ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI NEGERI SIPIL (PNS) - Andarias Patiran (STIE Pelita Nusantara Semarang, 2010)
The objective of this research is to observe the performance of the Civil Government Employees (PNS). This research will be carried out based on the observation that half of the civil government work seriously and half of them don’t work seriously. This condition certainly will influence the whole system implemented, so finally the objective of the local/province government to provide good service to the community cannot be achieved.Therefore, the researcher is interested to do the research about the performance of the civil servants which is dependent variable, by using 3 (three) independent variables (discipline, education and motivation) as instrument to measure dependent variable.